Extracellular Nucleotides ATP and UTP Induce a Marked Acute Release of Tissue-type Plasminogen Activator In Vivo in Man - Hrafnkelsdóttir, Thórdís; Erlinge, David; Jern, Sverker (Thrombosis and Haemostasis, 2001)
Extracellular nucleotides such as ATP and UTP are released by activation of platelets and ischemic tissue injury. The aim of the present study was to investigate whether ATP and UTP can induce acute tPA release from the vascular endothelium in vivo. Nine healthy subjects were studied in a perfused-forearm model during stepwise intraarterial infusions of ATP and UTP (10-200 nmol/min), and UTP during inhibition of prostanoid and NO synthesis by indomethacin and L-NMMA. ATP and UTP induced a similar and marked stimulation of forearm tPA release which increased 11- and 18-fold above baseline (p ≤ 0.01 for both) in conjunction with pronounced vasodilation. Neither the acute tPA release nor the vasodilation could be abrogated by NO and prostanoid synthesis inhibition. The similar effect of ATP and UTP suggests that P2Y rather than adenosine receptors mediate the response. Release of extracellular nucleotides in ischemic tissue may induce a pronounced activation of the endogenous fibrinolytic system.
Keywords: Vascular endothelium; tissue plasminogen activator; extracellular nucleotides; ATP; UTP; P2Y receptors